2015
DOI: 10.3892/mmr.2015.3146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melilotus suaveolens extract on pulmonary microvascular permeability by downregulating vascular endothelial growth factor expression in rats with sepsis

Abstract: A typical indicator of sepsis is the development of progressive subcutaneous and body-cavity edema, which is caused by the breakdown of endothelial barrier function, leading to a marked increase in vascular permeability. Microvascular leakage predisposes to microvascular thrombosis, breakdown of microcirculatory flow and organ failure, which are common events preceding mortality in patients with severe sepsis. Melilotus suaveolens (M. suaveolens) is a Traditional Tibetan Medicine. Previous pharmacological stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Despite advances in critical care in human medicine, sepsis and septic shock due to infection play considerable roles in the morbidity and mortality of patients in intensive care units, which has been reported to be between 30% and 50% ( 23 ). Consistent with the finding of Liu et al ( 13 ), the present study showed 100% mortality following the CLP model in rats. The high mortality rate recorded here may be due to severe blood loss that caused impaired oxygen delivery, leading to tissue dysfunction and finally death ( 1 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Despite advances in critical care in human medicine, sepsis and septic shock due to infection play considerable roles in the morbidity and mortality of patients in intensive care units, which has been reported to be between 30% and 50% ( 23 ). Consistent with the finding of Liu et al ( 13 ), the present study showed 100% mortality following the CLP model in rats. The high mortality rate recorded here may be due to severe blood loss that caused impaired oxygen delivery, leading to tissue dysfunction and finally death ( 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is therefore considered a gold standard tool for testing the success of CLP as a sepsis model, and for studying the efficacy of both SOBT and SOP extracts as novel antiseptic agents. In conjunction with the reports of Liu et al ( 13 ) and Tavares et al ( 27 ), data from the present investigation showed significantly increased PCT levels following CLP in rats. The increment of PCT in septic rats may be due to a continuous bulk-flow constitutive pathway, in which only limited conversion to mature calcitonin occurs ( 28 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cecal ligation and puncture is considered the most clinically applicable in vivo model for sepsis. The cecal ligation and puncture surgery was performed as designated by Liu et al (2015). Briefly, rats were anesthetized with an intraperitoneal injection of sodium pentobarbital (50 mg/ kg body weight) (Ho et al, 2015).…”
Section: Induction Of Sepsis By Cecal Ligation and Puncturementioning
confidence: 99%
“…Experimental procedures: Rats were subjected to either Cecal Ligation and Puncture (CLP) or sham operation using aseptic techniques, according to Liu et al 32 Eighteen rats were divided into two main groups, the sham-operated control (6 rats) and the CLP group (12 rats). Sodium pentobarbital (50 mg kgG 1 b.wt.)…”
Section: Experimental Animalsmentioning
confidence: 99%